Medical Student’s Attitudes towards Implementation of National Licensing Exam (NLE) – A Qualitative Exploratory Study: National Licensing Exam and Medical Students - Bashir, Saima; Khan, Rehan Ahmed (Pakistan Journal of Health Sciences, 2024)
The introduction of the post-qualification National Licensing Examination (NLE) in Pakistan has been met with resistance from the medical students. They are the main stakeholders of medical colleges. Objective: To explore the opinions of medical students regarding the feasibility of NLE. Methods: An exploratory, qualitative study was conducted at Riphah International University, Islamic international medical college, Rawalpindi and Gomal Medical College, D.I. Khan, KP using in-depth interviews. A sample of 12 medical students from different medical colleges in Pakistan was included. The recorded interviews transcribed verbatim. Thematic analysis was then conducted using NVivo V2 and coded into nodes and daughter nodes, of which 5 themes and 17 subthemes emerged. Results: A total of five themes and 17 themes were created. NLE was deemed as a good standardization tool for assessing the competence of medical graduates. Students believed that current MBBS assessment lacks in clinical skills assessment and did not prepare to treat patients upon graduation. However, they did not want to take another exam after the professional exams especially when no incentives are offered to graduates upon clearing. They suggested NLE should be used as a means of constructive feedback for institutions and students to allow them to work on weak areas. Conclusions: There were mixed opinions regarding the acceptance of the exam. If medical institutions across the country focus their curricula on developing clinical skills and incentives are provided to the doctors upon clearing, the students would readily accept the exam